Análisis de las exportaciones no tradicionales y su influencia en el crecimiento económico del Ecuador, en el periodo 1990 – 2021 - Romero Salinas, George Israel (2023)
This research analyzes the association between non-traditional exports and economic growth in Ecuador during 1990-2021, employing econometric methods and time series analysis. It was found that non-traditional exports experienced a relevant growth over time, contributing to the country's economic advancement. Moreover, a positive and significant correlation was identified between non-traditional exports and economic growth, suggesting that an increase in these exports is associated with higher economic growth. Furthermore, a significant unidirectional causality was identified from the economically active population to economic growth, highlighting the pivotal role of the labor factor in propelling economic growth in Ecuador. Consequently, it is recommended to focus economic policies on promoting and diversifying non-traditional exports, encouraging labor force participation, and improving workforce skills. In addition, augmenting investment in education and training is suggested to enhance the productivity and competitiveness of the Ecuadorian economy.